Idade de corte da silagem de capim elefante cv. Cameroon microbiota, inoculada com fungos autóctones do rúmen perdas composição química e pH - Henrique Fonseca Lopes (2022)
With this work, the objective was to determine the influence of autochthonous cellulolytic fungi from the bovine rumen on the microbiota, pH, chemical composition and losses of elephant grass cv. cameroon ensiled at 60 and 120 days of regrowth. The treatments were: control without additive at both cutting ages, inoculation with Aspergillus terreus at 60 (AT60) and 120 days of regrowth (AT120) applied at 1.0×105 colony forming units (CFU) per gram of natural matter (MN), Trichoderma longibrachiatum at 60 (TL60) and 120 days of regrowth (TL120) applied at 1.0×105 CFU/g of MN and these fungi combined at 1.0x105 CFU/g of forage MN at 60 (MIX60 ) and 120 days of regrowth (MIX120). After 56 days of ensilage, there was no difference between the microbiota of forage silages harvested at 60 days. The lactic acid bacteria (LAB) population was higher (P<0.05) for MIX120 5.50 log CFU/g MN compared to C120 3.60 log CFU/g MN. The parameters pH, gas losses and effluents were not influenced by the inoculation. In the silage made with cut grass at 60 days, the LAB populations showed negative correlations with fungi -0.370 (P<0.044) and gas losses -0.380 (P<0.037). Enterobacteria showed positive correlations with yeast count 0.369 (P<0.038). In the second silage LAB showed a positive correlation with pH 0.361 (P<0.050) and fungi also had a positive correlation with pH 0.395 (P<0.031). The use of fungi in elephant grass cv. cameroon harvested after 60 days of regrowth did not change the silage. This inoculum, when performed on forage harvested at 120 days of growth, provides greater development of Gram-positive bacilli and LAB.